A New Design for All-Normal Near Zero Dispersion Photonic Crystal Fiber with Selective Liquid Infiltration for Broadband Supercontinuum Generation at 1.55 μm. (16th April 2014) - Maji, Partha Sona; Roy Chaudhuri, Partha
Abstract : A new design of all-normal and near zero flattened dispersion based on all-silica photonic crystal fibers (PCFs) using selectively liquid infiltration technique has been proposed to realize smooth broadband supercontinuum generation (SCG). The investigation gives the details of the effect of different geometrical parameters along with the infiltrating liquids on the dispersion characteristics of the fiber. Numerical investigations establish a dispersion value of −0.48 ps/nm/km around the wavelength of 1.55  μ m. The optimized design has been found to be suitable for SCG around the C band of wavelength with flat broadband wavelength band (375 nm bandwidth) and smooth spectrum with only a meter long of the PCF. The proposed structure also demonstrates good tunable properties that can help correct possible fabrication mismatch towards a better optimization design for various optical communication systems.